2017
DOI: 10.1007/s12544-017-0226-z
|View full text |Cite
|
Sign up to set email alerts
|

Review of intermodal freight transportation in humanitarian logistics

Abstract: Purpose Using intermodal transportation is vital for the delivery of relief supplies when single mode alternative becomes unusable or infeasible. The objective of this paper is to investigate the use of intermodal freight transportation in humanitarian logistics. Methods This paper first identifies the differences between multimodal and intermodal transportation. Then, we examine the use of each transportation mode for specific disaster types and phases. When combinations of transportation modes (i.e. air, roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…We first identify the literature gap based on Ertem et al. [ 12 ]. Then, we investigate the features of commercial intermodal transportation that might be utilized in humanitarian logistics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first identify the literature gap based on Ertem et al. [ 12 ]. Then, we investigate the features of commercial intermodal transportation that might be utilized in humanitarian logistics.…”
Section: Methodsmentioning
confidence: 99%
“…IFT provides quicker service by reducing mode interchange times, thus utilizing humanitarian logistics (Ertem et al. [ 12 ]). Nevertheless, academic work on intermodal freight transportation and humanitarian logistics is not yet established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief review of relevant criteria from the literature is shown in Table 1. Distribution of service demand [66] Terminal charges [66] Modal shift [25,61,71] Economy of scale [11,76] Flexibility [1,11,60,72,77] Contribution to economic development [1,45,61] Availability [11,25,69] [1,61] International harmonization [45,50,59] Internalization of external costs [59,79] By reviewing the literature, no examples of scenario definition and evaluation for the development of IT systems were identified. According to this, the main contribution of this article is in defining IT system scenarios, as well as in defining the criteria set used for their evaluation.…”
Section: Review Of Relevant Criteria For Decision-making In the Area Of Itmentioning
confidence: 99%
“…Excessive transportation activities throughout an HSC require deploying different means of transport. Ertem et al (2017) reviewed transportation articles in HSCs and developed matrixes involving disaster type/phase and transportation mode. Their review show that most of humanitarian transportation is carried out via road.…”
Section: Procurement Transportation and Inventory Managementmentioning
confidence: 99%